Penerapan Metode Hierarchical Token Bucket Dalam Managemen Bandwidth Pada Pt Galempa Sejahtera Bersama - Liovi Egi Likardo; Khairil Khairil; Abdussalam Al Akbar (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Bandwidth management is necessary to ensure that the available bandwidth is allocated according to the needs of each connected user. One method that can stabilize the allocation of bandwidth is the Hierarchical Token Bucket (HTB) method. The purpose of this research is to regulate the amount of bandwidth to meet the internet usage requirements for each user without allowing any single user to dominate the bandwidth usage on the internet network. The research was conducted in five stages: problem analysis, data collection, design and implementation of HTB, HTB implementation, and analysis of the final results of the system using HTB. Problem analysis and data collection were obtained through direct observation. The design and implementation were carried out using the HTB method on MikroTik routers. The HTB method allows us to create queues in a more structured manner by performing hierarchical groupings. Testing results show that the HTB method can manage bandwidth usage for each user when using the internet simultaneously. The analysis of the application of the HTB method at PT. GSB indicates that each user receives bandwidth based on limit-at and priority.